2015
DOI: 10.1039/c5cp05466d
|View full text |Cite
|
Sign up to set email alerts
|

Band alignment and charge transfer in rutile-TiO2/CH3NH3PbI3−xClx interfaces

Abstract: Rutile-TiO2/hybrid halide perovskite CH3NH3PbI3-xClx interfaces are investigated by ab initio density functional theory calculations. The role of chlorine in achieving enhanced solar cell power conversion efficiencies is in the focus of recent studies, which point to increased carrier mobilities, reduced recombination rates, a driven morphology evolution of the perovskite layer and improved carrier transport across the interface. As it was recently established that chlorine is preferentially localized in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
6
12
0
Order By: Relevance
“…In a subsequent study, they reported a strong interfacial modification associated with the PbI 2 -terminated interface . First-principles investigations dealing with aTiO 2 (001)/MASn x Pb 1– x I 3 , rutile-TiO 2 (110)/MAPbI 3– x Cl x , amorphous-Al 2 O 3 /MAPbI 3 , and time-domain studies at aTiO 2 (001)/MAPbI 3 (100) have also been reported by several authors. …”
mentioning
confidence: 62%
“…In a subsequent study, they reported a strong interfacial modification associated with the PbI 2 -terminated interface . First-principles investigations dealing with aTiO 2 (001)/MASn x Pb 1– x I 3 , rutile-TiO 2 (110)/MAPbI 3– x Cl x , amorphous-Al 2 O 3 /MAPbI 3 , and time-domain studies at aTiO 2 (001)/MAPbI 3 (100) have also been reported by several authors. …”
mentioning
confidence: 62%
“…In fact, the surface energy differences at the termination border (μ CH 3 NH 3 = −2.55 eV, μ Pb = 0, μ Br = −1.41 eV and μ CH 3 NH 3 = −3.98 eV, and The band gap is a crucial material parameter for photovoltaic applications. Our calculations cannot predict quantitatively the magnitude of the band gap, due to the well-known deficiency of the GGA method [17,20,31,38]. However, we can make conclusions about changes in the band gap depending on the interface termination.…”
Section: A Surface Terminationmentioning
confidence: 91%
“…While there have been a number of theoretical efforts devoted to the studies of bulk CH 3 NH 3 PbX 3 materials, there are only a few theoretical reports discussing the properties of CH 3 NH 3 PbX 3 surfaces or interfaces. The latter mostly focus on the structural stability of CH 3 NH 3 PbI 3 surfaces of different orientations [27][28][29][30] or properties of the CH 3 NH 3 PbI 3 /TiO 2 interfaces [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…While the high PCEs and potentially low production costs are important assets, a number of challenges and open questions still need to be addressed. These concern especially the solar cell stability under ambient conditions [11], a better understanding of the device operation, and the optimization of the perovskite/substrate interface [12,13]. Furthermore, the J-V characteristics typically display hysteresis when measured under forward (short-circuit to open-circuit bias) and reverse bias scans [14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%